Off-Pump Coronary Artery Bypass Grafting in Dextrocardia with Situs Inversus Totalis – A Case Report - Johari, Raghav; Garg, M. (Journal of Nepalgunj Medical College, 2016)
Dextrocardia with situs inversus totalis, is a rare congenital condition. This goes undiagnosed many a times and is coincidentally diagnosed as in our case. Since individuals with this ailment have normal cardiac physiology and function, they live normal lives. We report one cases of dextrocardia (situs inversus totalis) with triple vessel coronary artery disease. To operate on patients with dextrocardia, surgeons need to make a few modifications. These include using the right internal mammary artery as a conduit for the “left” anterior descending artery, surgeons position - sometimes the operating surgeon may need to stand at the left side of the operating table or may have to come on left side for some time for positioning the heart and placing stabilizing device for optimum exposure. Pre-operative surgical difficulties which may be encountered and choice of conduits should be discussed beforehand. JNGMC Vol. 12 No. 2 December 2014, Page: 46-47